Characterization of multiple mRNA species of simian immunodeficiency virus from macaques in a CD4+ lymphoid cell line. - Park, I W (1991)
Cytoplasmic poly(A)+ RNA was isolated from CEMX721.174 cells 5 to 10 days after infection with molecularly cloned simian immunodeficiency virus SIVmac239. Expression of SIV RNA was analyzed by Northern (RNA) blot hybridization and by sequencing of cDNA clones. As expected, a splice donor site was demonstrated in the untranslated leader sequence outside the left long terminal repeat. The region between pol and env was found to contain at least two splice donor and six splice acceptor sites. Splice acceptor and donor sites in the intergenic region were suitably positioned for expression of vpx, vpr, tat, and rev. Splice acceptor sites at nucleotides 8802 and 8805 were demonstrated in singly and doubly spliced RNAs with the potential of expressing nef and the second exons of tat and rev. Our results demonstrate a complex pattern of alternative splicing of SIV mRNAs. The results are very similar to what has been observed in human immunodeficiency virus type 1-infected cells, suggesting that both human and simian immunodeficiency viruses are subject to multiple levels of regulation.